Eurotium cristatum Fermented Loose Dark Tea Ameliorates Cigarette Smoke-Induced Lung Injury by MAPK Pathway and Enhances Hepatic Metabolic Detoxification by PXR/AhR Pathway in Mice. (11th March 2021) - Huang, Xiang-Xiang; Xu, Shuai; Yu, Li-Jun; Zhou, Yu-Fei; Zhou, Ying; Liu, Zhong-Hua
Abstract : Cigarette smoke- (CS-) induced oxidative stress and inflammation in the lung are serious health problems. Primary and reprocessed tea products contain multiple antioxidants that have been reported to protect the lung against CS-induced injury. However, the beneficial effects of Eurotium cristatum fermented loose dark tea (ECT) and Eurotium cristatum particle metabolites (ECP) on CS-induced lung injury and its potential hepatic metabolic detoxification are still unclear. Therefore, sixty mice were randomly divided into six equal groups. CS-exposed mice were prevented or treated with ECP or ECT infusions for 12 or 8 weeks to determine the antioxidative stress, anti-inflammatory and potential metabolic detoxification of ECT and ECP. Thirty-six mice were randomly divided into six equal groups to observe the effects on hepatic metabolic detoxification by replacing daily drinking water with ECT. Results showed that CS significantly decreased the activities of glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) and upregulated the expressions of malondialdehyde (MDA), tumor necrosis factor alpha (TNF- α ), interleukin-6 (IL-6), IL-8, and IL-1 β in serum. These adverse effects were modulated by ECP and ECT. In addition, ECT upregulated the mRNA expression of pregnane X receptor ( PXR ) and cytochrome P450 ( CYP450 ) in the liver on daily free drinking ECT mice group. Western blot analysis further revealed that in CS-exposed mice, ECP and ECT significantly decreased the phosphorylation of mitogen-activated protein kinase (MAPK) in the lung but upregulated the protein expressions of PXR and aryl hydrocarbon receptor ( AhR ) in the liver. Overall, our findings demonstrated that ECT and ECP protected against lung injury induced by CS via MAPK pathway and enhanced hepatic metabolic detoxification via PXR and AhR pathways. Therefore, daily intake of ECT and ECP can potentially protect against CS-induced oxidative and inflammatory injuries.